Ղունկիանոս Երգիչ Կարնեցի. «Այլ եւ այլք» - Արիադնա Հարությունյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В XVIII веке значительно возрастает роль духовного песнопения: она проникается бытом и становится более жизненной и понятной, придавая новое звучание поэзии.In the 18th century, the signifi cance of spiritual songs increased in many ways, which reinforced the ties between literature, having already a social function, and life with its fresh and interesting nuances.
Keywords: Literature